(untitled) (Research, Society and Development, 2020)
Giant Cell Peripheral Granuloma (GPCG), corresponds to one of the most common lesions of the oral cavity, presenting as an exophytic lesion, sessile or pediculated, of soft or gelatinous consistency with red, purple – blue or purple coloration, usually asymptomatic. Currently, GPCG has a high frequency in women, in the gingiva or in the mandibular alveolar crest, with preference for the molar region. Its etiopathogenesis has not been fully clarified, but it is estimated to have its origin in the gingival connective tissue or in the alveolar process, related to local irritating agents. In order to discern the differential diagnosis, some complementary exams are requested, such as panoramic radiography and, shortly after the biopsy, the histopathological exam, thus the ideal treatment for GPCG is surgical with a positive prognosis. The aim of this study is to report a case of a female patient who has GPCG in the gingival mucosa, in the mandibular ridge and had the lesion surgically removed with safety margins, associated with the removal of irritating factors.